A virtual laboratory for the simulation of sustainable energy systems in a low energy building: A case study. Issue 1 (March 2016) - Breen, M; O'Donovan, A; Murphy, M D; Delaney, F; Hill, M; Sullivan, P D O
Abstract: The aim of this paper was to develop a virtual laboratory simulation platform of the National Building Retrofit Test-bed at the Cork Institute of Technology, Ireland. The building in question is a low-energy retrofit which is provided with electricity by renewable systems including photovoltaics and wind. It can be thought of as a living laboratory, as a number of internal and external building factors are recorded at regular intervals during human occupation. The analysis carried out in this paper demonstrated that, for the period from April to September 2015, the electricity provided by the renewable systems did not consistently match the building's electricity requirements due to differing load profiles. It was concluded that the use of load shifting techniques may help to increase the percentage of renewable energy utilisation.